2023
DOI: 10.4103/ijmr.ijmr_1090_21
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of treatment-free remission with generic imatinib

Abstract: Background & objectives: Both innovator and generic imatinib are approved for the treatment of Chronic Myeloid Leukaemia-Chronic phase (CML-CP). Currently, there are no studies on the feasibility of treatment-free remission (TFR) with generic imatinib. This study attempted to determine the feasibility and efficacy of TFR in patients on generic Imatinib. Methods: In this single-centre prospective Generic Imatinib-Free Trial-in-CML-CP study, twenty six patients on generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 23 publications
1
2
0
Order By: Relevance
“…Our study showed a 12-month overall mean TFR rate of 60% [95CI:0.56-0.63] and a 24-month overall mean TFR rate of 55% [95CI:0.52-0.59], indicating that more than half of the CML-CP patients were able to maintain TFR two years after TKI discontinuation. Our subgroup analysis showed that better TFR was associated with prior interferon therapy (12months: P < 0.001,24months: P = 0.006), and molecular response depth MR5.0 (12months:P = 0.005,24months: P = 0.02), which is in line with the ndings of previous trials [23,33,35] , although this analysis exists heterogeneity. According to the previous study [15] , the duration of DMR and TKI therapy before discontinuation were found to be associated with TFR.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our study showed a 12-month overall mean TFR rate of 60% [95CI:0.56-0.63] and a 24-month overall mean TFR rate of 55% [95CI:0.52-0.59], indicating that more than half of the CML-CP patients were able to maintain TFR two years after TKI discontinuation. Our subgroup analysis showed that better TFR was associated with prior interferon therapy (12months: P < 0.001,24months: P = 0.006), and molecular response depth MR5.0 (12months:P = 0.005,24months: P = 0.02), which is in line with the ndings of previous trials [23,33,35] , although this analysis exists heterogeneity. According to the previous study [15] , the duration of DMR and TKI therapy before discontinuation were found to be associated with TFR.…”
Section: Discussionsupporting
confidence: 90%
“…A total of 19 trials [23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41] involving 2336 patients were included in this meta-analysis. Eight trials have investigated the probability of TFR after imatinib treatment [23,25,32,36,[39][40][41] , four trials have investigated the probability of TFR after dasatinib treatment [24,[28][29][30] , three trials have investigated the probability of TFR after nilotinib treatment [26,34,37] , and the remaining four trials have investigated the probability of TFR after treatment with different TKIs [27,31,33,38] . There were no clinical trials related to the discontinuation of umatinib, third-generation TKIs, etc., and only the LAST, GIMEMA CML0307 trial had 7 patients on bosutinib [26,27] .…”
Section: Study Characteristicsmentioning
confidence: 99%
“…Eighteen patients remained in continuous TFR, and no patient progressed to the advanced phase, suggesting long-term safety and remarkable stability of response after imatinib discontinuation in appropriately selected CML patients [ 57 ]. A recent report by Goni et al recruited 26 CML patients on generic imatinib for ≥3 years and in sustained deep molecular response, where the median follow-up was 33 months, and 42.3% continued to be in TFR, with all patients who restarted on generic imatinib regaining a major molecular response [ 58 ]. A similar approach in 190 CML Chinese patients enrolled in the TFR protocol showed a success rate of 76.9% (95% CI, 70.2–82.4%), 68.8% (95% CI, 61.3–75.2%), and 65.5% (95% CI, 57.4–72.5%) at 6, 12, and 24 months after stopping TKI, and 98.2% of patients who needed to restart TKI treatment quickly achieved MMR [ 59 ].…”
Section: Discussionmentioning
confidence: 99%